Preparation and in vitro investigation on bioactivity of magnesia-contained bioactive glasses - Arepalli S.K.; Tripathi H.; Manna P.P.; Pankaj P.; Krishnamurthy S.; Patne S.C.U.; Pyare R.; Singh S.P. (My University, 2025)
Mg plays an important role in the human skeletal system as it stimulates the bone formation and reduces bone resorption. Magnesium has been substituted into SiO 2 –Na 2 O–CaO–P 2 O 5 bioactive glass. In the present work, the bioactive glasses were designed to enhance bioactivity. Bioactivity of these glasses was assessed by the immersion of the samples in simulated body fluid (SBF) for different time periods. The formation of hydroxy carbonate apatite (HCA) layer was confirmed by scanning electron microscopy, X-ray diffractometry, and FTIR spectrometry which had shown the HCA layer formation and growth. The formation of HCA layer was found to increase on the surface of the SBF immersed bioactive glasses with increasing magnesia contents in the glass. In vitro cell culture investigations such as viability, proliferation, and cell attachment were studied using human osteosarcoma U2-OS cell lines. The in vitro results of new magnesium containing bioactive glasses had shown improved bioactivity as well as better biocompatibility. © 2018, Australian Ceramic Society.